(untitled) (2014)
Calliphorids are the first arthropods to colonize cadavers, their composition and abundance vary according to location. They are used to estimate post-mortem intervals and surmise the relocation of corpses; making the identification of these local variations are key in detecting the relocation of a body. We assessed these blowfly variations in 11 sites in Bogotá. A pre-sampling (dry season) was conducted to select a trapping method and sampling sites; the formal sampling (rainy season) was conducted using a directed sweep net. We identified the following species: Lucilia sericata, Roraimomusca roraima, Compsomyiops verena, Calliphora nigribasis, Calliphora vicina and Sarconesiopsis magellanica and compared their richness, diversity, dominance and composition for each site. The highest richness was found in Chico-Lago (Chico) while the lowest was Alcazares (Barrios Unidos). Bolivia (Engativá) was the most diverse and 20 de Julio (San Cristobal) the least; dominance was higher in 20 de Julio and lower in Apogeo (Bosa). Species’ composition and abundance varied between sites; this may be used as evidence to support cases in Bogotá in which cadavers have been relocated.